The Development Of Digital-Based Question Card Media On Students’ Ability To Understand Pancasila Values At Annysa Private Elementary School - Salsabila Alfisyah; Mastari Ramadhani; Nizmi Putri (Journal Innovative Practices in Education (JIPE), 2026)
This study aimed to develop digital-based question card media and to examine its effectiveness in improving students’ ability to understand Pancasila values at Annysa Private Elementary School. The study employed a Research and Development (R&D) method using the ADDIE model, which consisted of analysis, design, development, implementation, and evaluation stages. The research subjects were fourth-grade students. The instruments used included expert validation sheets, student and teacher response questionnaires, as well as pretest and posttest assessments. The results indicated that the developed media was categorized as highly feasible based on evaluations by material, language, and media experts. During the implementation stage, there was a significant improvement in students’ learning outcomes, with the average pretest score of 52.55 increasing to 80.95 in the posttest. In addition, student and teacher responses to the use of the media were categorized as very good. The digital-based question card media also enhanced students’ engagement, motivation, and active participation in the learning process. Thus, the developed media proved to be effective and could be used as an innovative alternative in Civics (PPKn) learning to help students understand and internalize Pancasila values in a more contextual and applicable manner in their daily lives.